Mathematics: the bottleneck of cancer research - Win, Shoon Lei; Htike@Muhammad Yusof, Zaw Zaw; Yusof, Faridah; Noorbatcha, Ibrahim Ali (2014)
Cancer is a type of disease typified by uncontrolled cell division. Cancer is a major leading cause of death and responsible for around 13% of all deaths world-wide. There have been various attempts by researchers to understand, diagnose, and cure cancer. There have been numerous advances in terms of high-throughput technology such as lab-on-a-chip, electrophoresis, and microarray technology. Because of these advances, there is a persistent need to analyze complex data from these devices. The mathematical analysis technology has been lagging behind the sensing technology. This paper reviews state-of-the-art mathematical techniques utilized in cancer research and posits that mathematics is a bottleneck in all the five areas of cancer research starting from carcinogenesis all the way to therapeutics. Mathematical modeling and analysis play a pivotal role in cancer research. Carcinogenesis can be best understood in terms of mathematics. Despite the fact that cancer is preventable and curable in early stages, the vast majority of patients are diagnosed with cancer very late. Therefore, it is of paramount importance to prevent and detect cancer early. Mathematics always plays a great role in analyzing metabolomic, proteomic, transcriptomic, and genomic data in order to perform diagnosis and prognosis. Moreover, cancer treatment and therapeutics also require mathematical modeling.